2021
DOI: 10.3390/ijerph18052641
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Identity Conflict Informs Engagement with Self-Management Behaviours for South Asian Patients Living with Type-2 Diabetes: A Critical Interpretative Synthesis of Qualitative Research Studies

Abstract: The prevalence of type-2 diabetes (T2D) is increasing, particularly among South Asian (SA) communities. Previous research has highlighted the heterogeneous nature of SA ethnicity and the need to consider culture in SA patients’ self-management of T2D. We conducted a critical interpretative synthesis (CIS) which aimed to a) develop a new and comprehensive insight into the psychology which underpins SA patients’ T2D self-management behaviours and b) present a conceptual model to inform future T2D interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…SA patients are thought to consider T2D as a social norm (Social Norm Theory, Perkins & Berkowitz, 1986) within their community, a given disease, for which they have limited behavioural influence. This finding is congruent with research exploring the beliefs of SA patients living with T2D (Patel et al, 2021). HPs suggested that patients made social comparisons (Social Comparison Theory, Festinger, 1954) towards others with and without T2D and compared T2D against other health diseases (such as cancer).…”
Section: Core Category: Cultural Conflict In T2d Caresupporting
confidence: 75%
See 2 more Smart Citations
“…SA patients are thought to consider T2D as a social norm (Social Norm Theory, Perkins & Berkowitz, 1986) within their community, a given disease, for which they have limited behavioural influence. This finding is congruent with research exploring the beliefs of SA patients living with T2D (Patel et al, 2021). HPs suggested that patients made social comparisons (Social Comparison Theory, Festinger, 1954) towards others with and without T2D and compared T2D against other health diseases (such as cancer).…”
Section: Core Category: Cultural Conflict In T2d Caresupporting
confidence: 75%
“…Difficulties in managing such conflict interfere with their interpretation and alignment to any advice received from HPs. As such, SA patients may prioritise their cultural identity before that of their health and T2D status, which may negatively impact their self-management behaviours (Patel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identi ed that patients' perceptions of diabetes diagnosis could determine the motivation of self-management engagement [19][20][21][22][23] Suglo and Evans 2012). People who accepted their own diagnosis of diabetes and perceived the diagnosis as a severe condition could be motivated to engage in self-management to achieve better diabetes control engagement [19][20][21][22][23]. However, perception of diabetes diagnosis could be culturally sensitive engagement [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and interpretative synthesis highlights the complex nature of self-management of T2DM. Making lifestyle changes is challenging, and understanding and accounting for the context in which people live, their social influences, cultural and societal norms, the physical environment, and physiological and psychological factors are important [7].…”
Section: Introductionmentioning
confidence: 99%